Adsorption of dyes solution on commercial activated carbon adsorbent : continuous - Mohamad Nazmin B. Md. Husain (School of Environmental Engineering University Malaysia Perlis, 2011)
The sorption of two methyl dyes, namely, methyl Red (C14H14N3NaO3S), and methyl orange (C14H14N3NaO3S), on activated carbon, has been studied. Three parameters has been studied ; i.) effect of initial concentartion, (50, 100, 150 mg/L) with costant bed high, 80 mm and constant initial concentration, 100mg/L iii and effect of bed height (60, 100 mm) with constant flow rate 15mL/min and constant initial concentration100mg/L. The removal of dye was faster in initial stages, gradually decrasing pattern and became constant after equilibrium was achieved. The initial dye concentration of the effluent is important since a given mass of adsorbent can only adsorb a fixed point amount of dye.